Marine-Derived Biomaterials for Tissue Engineering Applications - Choi, Andy H.; Ben-Nissan, Besim; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the latest advances in marine structures and related biomaterials for applications in both soft- and hard-tissue engineering, as well as controlled drug delivery. It explores marine structures consisting of materials with a wide variety of characteristics that warrant their use as biomaterials. It also underlines the importance of exploiting natural marine resources for the sustainable development of novel biomaterials and discusses the resulting environmental and economic benefits. The book is divided into three major sections: the first covers the clinical application of marine biomaterials for drug delivery in tissue engineering, while the other two examine the clinical significance of marine structures in soft- and hard-tissue engineering, respectively. Focusing on clinically oriented applications, it is a valuable resource for dentists, oral and maxillofacial surgeons, orthopedic surgeons, and students and researchers in the field of tissue engineering. .
Ecological and Environmental Issues Concerning the Use of Marine Structures in Tissue Engineering -- Marine Biomaterials and Tissue Engineering -- Brown algal polyphenol and its pharmaceutical properties -- Marine Nanopharmaceuticals for Drug Delivery and Targeting -- Composites Containing Marine Biomaterials for Bone Tissue Repair -- Chitin Nanomaterials and Nanocomposites for Tissue Repair -- Marine Polysaccharides: Biomedical and Tissue Engineering Applications -- Hydroxyapatite scaffolds produced from cuttlefish bone via hydrothermal transformation for application in tissue engineering and drug delivery systems -- Chitosan-Based Biocomposite Scaffolds and Hydrogels for Bone Tissue Regeneration -- Clinical Application of Biomimetic Marine-Derived Materials for Tissue Engineering -- Conversion of Red Coral to Calcium Phosphate For Drug Delivery and Tissue Engineering Applications -- Marine Sponges for Soft and Hard Tissue Engineering -- Marine Inspired Biomaterials on Tissue Engineering approaches -- Bone Tissue Scaffold Utilizing Sea Urchin -- Medical Application of Rift-Algae Recoverable at Reef -- Nanobiomaterial Derived from Marine Products for Bone Tissue Engineering -- Production of Nano-Hydroxyapatite Powder using Marine Shells -- Biomaterial from Fish for Bone Tissue Engineering: Conversion and Application -- Hydroxyapatite from Marine Fish and Giant Purple Barnacle -- Calcified Algae for Tissue Engineering -- Synthesis of Nanoscale Functional Materials from Marine Blueprints for Bone Tissue Engineering.
Keywords: Biomaterials; Materials; Regenerative medicine; Biotechnology; Biomedical engineering; Biomaterials; Materials Engineering; Regenerative Medicine and Tissue Engineering; Biotechnology; Biomedical Engineering and Bioengineering